The role of neoadjuvant conventional transarterial chemoembolization with radiofrequency ablation in the treatment of recurrent hepatocellular carcinoma after initial hepatectomy with microvascular invasion. (31st December 2022) - Peng, Zhenwei; Wu, Xiaoxue; Li, Jiaping; Pang, Hui; Zhang, Yaojun; Lin, Manxia; Wang, Zaiguo; Xiao, Han; Li, Bin; Chen, Minshan; Feng, Shiting; Kuang, Ming; et al.
Abstract: Objectives: Recurrent hepatocellular carcinoma (HCC) patients with microvascular invasion (MVI)-positive primary tumor is at high risk of re-recurrence while treated with radiofrequency ablation (RFA). We aimed to investigate whether neoadjuvant conventional transarterial chemoembolization (cTACE) was effective in reducing re-recurrence after RFA for recurrent HCC patients with MVI-positive primary tumors. Methods: In this retrospective multicenter study, 468 patients with solitary small recurrent HCC (≤3.0cm) underwent RFA alone ( n  = 322) or with neoadjuvant cTACE ( n  = 146) between June 2007 and December 2017 were included. Overall survival (OS) and recurrence-free survival (RFS) were compared. Results: The 1-, 5-year OS rates were 74.8%, 42.5% for RFA with neoadjuvant cTACE group, and 53.5%, 28.7% for RFA group ( P  < 0.001). The corresponding RFS rates were 51.7%, 24.4% for RFA with neoadjuvant cTACE group, and 36.1%, 9.3% for RFA group ( P  < 0.001). In subgroup analyses, the OS and RFS for neoadjuvant cTACE group were longer than those for RFA group no matter tumor size > 2cm (HR = 0.52, 95% CI: 0.36–0.77; HR = 0.49, 95% CI: 0.36–0.67) or not (HR = 0.53, 95% CI: 0.32–0.88; HR = 0.65, 95% CI: 0.42–0.98), or the time interval of recurrence from initial treatment ≤ 1 year (HR = 0.53, 95% CI: 0.36–0.77; HR = 0.70, 95% CI: 0.52–0.94) or not (HR = 0.56, 95% CI: 0.34–0.95; HR = 0.39, 95% CI: 0.25–0.62). Multivariable analyses showed that RFA alone (HR = 1.329, P  = 0.031; HR = 1.764, P  = 0.004) and interval of recurrence from initial treatment > 1 year(HR = 0.642, P  = 0.001; HR = 0.298, P  = 0.037) were independent prognostic factors of OS and RFS. Conclusions: Neoadjuvant cTACE could effectively reduce re-recurrence after RFA, and improve the long-term survivals for patients with solitary small recurrent HCC whose primary tumor was MVI-positive. Key points: For recurrent hepatocellular carcinoma (HCC) patients whose primary tumor was positive for microvascular invasion, neoadjuvant conventional transarterial chemoembolization (cTACE) with radiofrequency ablation (RFA) achieved better efficacy. Multivariable analyses showed that the interval of recurrence from initial treatment > 1 year and RFA alone were independent prognostic factors of overall survival and recurrence-free survival, respectively.